2015
DOI: 10.1007/s11325-015-1227-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome: coagulation anomalies and treatment with continuous positive airway pressure

Abstract: Further studies are required to determine the precise role of hypercoagulability in the cardiovascular pathogenesis of OSAS, particularly its interaction with oxidative stress, thrombotic tendency and endothelial dysfunction. Nasal continuous positive airway pressure (nCPAP), the gold standard treatment for OSAS, not only significantly reduced apnea-hypopnoea indices but also markers of hypercoagulability, thus representing a potential mechanisms by which CPAP reduces the rate of cardiovascular morbidity and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 92 publications
1
16
0
2
Order By: Relevance
“…CIH is an important physiological mechanism that could link OSA to vascular, cerebral, and neurocognitive deficits [ 35 , 36 , 37 , 38 , 39 , 40 ]. In particular, oxidative stress induced by CIH and increased blood clotting (caused by changes in the rheological properties of blood and plasma) are important physiological mechanisms of the disease and cause cerebrovascular complications and impairments in several brain regions [ 37 , 38 , 39 , 41 , 42 , 43 ]. Thus, hypoxia is considered to be the main factor underlying neurocognitive deficits in OSA (for a recent meta-review, see [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…CIH is an important physiological mechanism that could link OSA to vascular, cerebral, and neurocognitive deficits [ 35 , 36 , 37 , 38 , 39 , 40 ]. In particular, oxidative stress induced by CIH and increased blood clotting (caused by changes in the rheological properties of blood and plasma) are important physiological mechanisms of the disease and cause cerebrovascular complications and impairments in several brain regions [ 37 , 38 , 39 , 41 , 42 , 43 ]. Thus, hypoxia is considered to be the main factor underlying neurocognitive deficits in OSA (for a recent meta-review, see [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated that patients with T2D and diabetic foot syndrome have lower mean values of RHI than diabetic subjects without diabetic foot [23]. OSA is also associated with a decrease in endothelial NO synthase and an increase in endothelin-1 levels [24], with hypercoagulability [25], and inflammation [26]. Repeated hypoxemia-reoxygenation episodes induce ROS production [27].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, OSA can impact the platelet function 7, 8. Gunbey et al have found that platelet aggregation was correlated with apnea‐hypopnea index (AHI) 9.…”
mentioning
confidence: 99%